Ministry of Agriculture's Public Relations Strategy Through the Millennial Farmer Program - Ananto Akbar; Nurul Hidayah; Rani Chandra Oktaviani; Febrina Ramadyanti (Communicare : Journal of Communication Studies, 2022)
Currently, Indonesia is facing the threat of a crisis in the agricultural sector. The decrease in the number of farmers was due to the low wages of workers in the agricultural sector, which were the lowest compared to the wages of workers in other sectors. The public relations task of the Ministry of Agriculture is to make agriculture more modern to attract the younger generation to enter the world of agriculture. The purpose of this study was to determine the extent of the Ministry of Agriculture's public relations strategy in creating food security through the millennial farmer program and to analyze the weaknesses of the Ministry of Agriculture's public relations strategy in creating food security through the millennial farmer program. The research method used is a descriptive study with a qualitative approach. The results showed that the Ministry of Agriculture's public relations strategy by conducting press relations, government relations, customers relations, maximized the public relations function (maintain good communication, serve public's interest, maintain good morals and manners). The weakness of the Ministry of Agriculture's public relations strategy has not been maximal in carrying out its duties related to the millennial farmer program. This is evidenced by doing the following: providing understanding to the community about millennial farmers, providing understanding to the community about institutions, providing understanding to the community about goals, providing understanding to the community about activities, maintaining good relations with the community regarding millennial farmers.